DESAIN DAN EFEKTIVITAS VIDEO PEMBELAJARAN PADA PENDIDIKAN VOKASIONAL: SYSTEMATIC LITERATURE REVIEW BERBASIS PRISMA 2020 UNTUK MENDUKUNG MATERI PERAWATAN SISTEM KEMUDI, REM, DAN SUSPENSI - Zifa Oktavianza; Toto Sugiarto; Wagino Wagino; Ahmad Arif; Muslim Muslim (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study presents a systematic literature review (SLR) on the trends, design, and effectiveness of instructional videos in the context of education, procedural learning, and vocational education relevant to the development of steering, brake, and suspension system maintenance materials on 4-stroke cub motorcycles. The data source comes from a Scopus tabulation of 1,400 records. Selection was carried out using the PRISMA 2020 flow based on article metadata (title, author, year, source, document type, and citation). After duplications were removed, screening was limited to articles/reviews from the 2020–2025 period, then thematic relevance screening was carried out to obtain 50 articles for the final synthesis. The review results indicate four dominant themes, namely: (1) instructional video design and effectiveness; (2) interactivity, flipped learning, and YouTube; (3) VR/AR and practicum media; and (4) TVET/vocational and implementation readiness. The synthesis shows that effective instructional videos are characterized by good material segmentation, appropriate visual cues, proportional instructor presence, planned interactivity, and integration with practical or reflection tasks. Furthermore, VR/AR has the potential to enhance procedural learning, but requires cognitive load management. In a vocational context, the quality of implementation is strongly influenced by teachers' digital competencies, digital pedagogical policies, and the relevance of job skills. These findings lead to recommendations for developing automotive learning videos that are concise, procedural, multimodal, problem-based, and integrated with practical evaluation.Keywords: learning videos, instructional videos, vocational education, TVET, PRISMA 2020, virtual reality, YouTube, automotive